2009
DOI: 10.1016/j.jvs.2008.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after endovascular stent graft repair of aortoenteric fistula: A systematic review

Abstract: Endovascular stent graft repair of AEF was associated with a high incidence of infection or recurrent bleeding postoperatively. Evidence of sepsis preoperatively was indicating poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 43 publications
2
118
0
15
Order By: Relevance
“…Several reports have described the endovascular repair of AEFs. Antoniou et al 5) observed a graft infection or recurrent bleeding in 44% of mid-to long-term venous morbidity after an FV harvest is minimal. 17) The major drawback to this technique is the long operation time.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the endovascular repair of AEFs. Antoniou et al 5) observed a graft infection or recurrent bleeding in 44% of mid-to long-term venous morbidity after an FV harvest is minimal. 17) The major drawback to this technique is the long operation time.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the possible development of local infection and aggravation of sepsis, favorable longer-term outcomes cannot be expected. 14) On the other hand, the short-term results and longterm outcomes of radical surgery using in situ vascular reconstruction were favorable, and we consider this procedure as the standard surgical procedure for sAEFs. Endovascular stent graft repair can be chosen as an emergency evacuation measure to control bleeding for shock; but even in such cases, radical surgery should be performed as soon as possible after stabilization of the patient's general condition.…”
Section: Disclosure Statementmentioning
confidence: 95%
“…Favorable longer-term outcomes cannot be expected due to the recurrence of sepsis. 14) In our department, sAEFs have been treated by complete resection of the infected graft and intestinal fistula with in situ vascular reconstruction, with favorable results. In this study, we evaluated the results of in situ reconstruction in 10 patients with sAEFs treated between 2009 and 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies continuously demonstrated that EVAR is a possible alternative procedure for infected aortic aneurysm patients with high surgical risks, with an early mortality rate less than 20%, which is comparable to that of traditional open repair. A poorer outcome was still evident in patients with aneurysm-related fistulation complication [71,72,[124][125][126][127]. Persistent infection greatly contributed to both early and late mortalities; thus, adjunctive procedures to eliminate contamination and prolonged antibiotic therapy duration after EVAR were usually advocated in the literatures [18,72,74] (see more details in Sections 7.4 and 7.5).…”
Section: Endovascular Techniquementioning
confidence: 99%